2008
DOI: 10.1063/1.2901160
|View full text |Cite
|
Sign up to set email alerts
|

Optical band gap of BiFeO3 grown by molecular-beam epitaxy

Abstract: BiFeO 3 thin films have been deposited on ͑001͒ SrTiO 3 substrates by adsorption-controlled reactive molecular-beam epitaxy. For a given bismuth overpressure and oxygen activity, single-phase BiFeO 3 films can be grown over a range of deposition temperatures in accordance with thermodynamic calculations. Four-circle x-ray diffraction reveals phase-pure, epitaxial films with rocking curve full width at half maximum values as narrow as 29 arc sec ͑0.008°͒. Multiple-angle spectroscopic ellipsometry reveals a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

35
226
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(263 citation statements)
references
References 30 publications
(29 reference statements)
35
226
2
Order By: Relevance
“…4(a)]. For LSDA þ U, we have chosen U eff ¼ 3:0 eV, which gives a direct band gap of 2.5 eV at the À point, compared to the experimental direct band gap of 2.7 eV [24]. The calculated indirect gap is reduced from 1.7 to 0.74 eV on suppressing the octahedral tilts; the ground state remains G-type antiferromagnetic and insulating [ Fig.…”
mentioning
confidence: 99%
“…4(a)]. For LSDA þ U, we have chosen U eff ¼ 3:0 eV, which gives a direct band gap of 2.5 eV at the À point, compared to the experimental direct band gap of 2.7 eV [24]. The calculated indirect gap is reduced from 1.7 to 0.74 eV on suppressing the octahedral tilts; the ground state remains G-type antiferromagnetic and insulating [ Fig.…”
mentioning
confidence: 99%
“…41 The band gap in a T-BFO thin film is approximately 2.89 ± 0.01 eV, which is significantly smaller than that of T-like BFO on LAO (∼3.12 eV) 42 and larger than that of R-BFO on STO (2.77-2.82 eV). 42,43 Noteworthily, it has been known that the band gap of BFO is almost independent to its strain when it is still keeps the same phase. 43 Therefore, it implies that the observed difference in energy gap is phase-dependent, suggesting that the T-BFO found in this study should be different, the common cases of T-like BFO.…”
mentioning
confidence: 99%
“…42,43 Noteworthily, it has been known that the band gap of BFO is almost independent to its strain when it is still keeps the same phase. 43 Therefore, it implies that the observed difference in energy gap is phase-dependent, suggesting that the T-BFO found in this study should be different, the common cases of T-like BFO. Moreover, with an increase in the temperature, an anomaly in the band gap was observed at approximately 670 K (Fig.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The optical properties of BiFeO 3 (BFO) are also different from most of the perovskite ferroelectric due to its lower bandgap (2.6-2.9 eV) and conducting domain walls. 11,12 Clark and Robertson 13 predicted both direct and indirect bandgaps around 2.5 eV using band structure model, and afterward Ihlefeld et al 14 reported a direct-gap transition at 2.74 eV; however, recently we also found a direct bandgap of 2.55 eV at T ¼ 295 K, an indirect band edge at 2.67 eV. 5 Conventional photoelectric (PE) devices are based on two basic principles: first, the generation of electrical charge carriers in the active medium under the illumination of light; and second, separation and detection of photoinduced charge carriers by in-built asymmetric potential of p-n junction or Schottky junction or difference in work function between electrodes and semiconductor.…”
mentioning
confidence: 99%